Sleep, social media use and mental health in female adolescents aged 12 to 18 years old during the COVID-19 pandemic - Wikanda Chalermchutidej; Boonying Manaboriboon; Gornmigar Sanpawitayakul; Supparat Theppiban; Supinya In-iw (BMC, 2023)
Abstract Background Adolescents with high social media (SM) use experienced poor sleep quality and high anxiety and depression levels. The study aimed to investigate the characteristics of sleep, use of SM, mental health in female aged 12 to 18 years old, and to assess the association between poor sleep, SM usage, and mental health. Methods In total, 219 Thai female adolescents were recruited between December 2019 and September 2020 and completed self-administrative questionnaires three periods of time (baseline, 3 months and 6 months later). The questionnaires included: the Pittsburgh Sleep Quality Index (PSQI), depression screening (PHQ-9), Screen for Child Anxiety Related Emotional Disorders (SCARED). Demographic and use of social media data were also included. Cochran's Q test, correlation coefficient, and binary logistic regression were performed. Results Participants' mean age was 14.52 (range 12-17) years. Average Thai-PSQI global scores did not differ during 3 periods (p = 0.13) but average time of sleep latency, sleep duration, and SM usage were significant different (p = 0.002, p = 0.001, and p = < 0.001, respectively). There were positive correlations between PSQI scores and total SM usage at baseline (r = 0.14; P < 0.05) and 6 months (r = 0.20; P < 0.05). Anxiety, depression, and self-perception of poor sleep were significantly related to poor sleep quality during the 3 periods. After adjusting for confounding factors, depression and self-reported poor sleep were the only significant factors predicting poor sleep quality. Conclusions Poor sleep was associated with SM usage, depression, and anxiety in this population. Time-limited SM usage should be implemented for Thai female adolescents to improve sleep-related outcomes.